Computer Science Intensive Intervention to Prepare and Engage Underrepresented Novice Students at Community College. Issue 8 (3rd August 2022) - Lyon, Louise Ann; Schatz, Colin; Toyama, Yukie; Torres, David
ABSTRACT: As open-access institutions serving diverse student populations, community colleges are perfect settings for broadening participation in computing efforts in higher education. The very nature of open access, however, places students with a wide variety of previous experience in the same introductory computer science classroom, intimidating the students with little programming exposure, many of whom are traditionally underrepresented in computer science. This paper reports on a pre-semester, intensive program designed to increase the computer science confidence and motivation of students with no previous programming exposure implemented at a community college in California. Framed using social cognitive career theory, results from the accompanying research project indicate preliminary success; we found the program to be well received by the majority of students, who had increased self-efficacy and interest in computer science. Implications for practice and research are discussed.